Outcome of Pcnl in Proximal Ureteric Stone: A Comparative Study With Laparoscopic Retrieval - Ahmed, Tanvir; Kabir, Md Humayun; Md Khairuzzaman, -; Ahsan, Md Monirul; Jahan, Mirana; Islam, Md Sayedul (Bangladesh Journal of Urology, 2020)
A hundred-percent stone clearance was achieved in a hospital based prospective clinical trial in which 60 cases of upper ureteric stone were selected by purposive sampling for percutaneous nephroureterolithotomy & Laparoscopic ureterolithotomy between December 2012 and June 2014 in BSMMU. The mean age of the patients was 40.53±11.71 (19-61) and 41.23±10.76 (20-59) years old in PCNUL and LUL groups, respectively. The mean stone size in PCNUL group was 1.88±0.39 (1.06-2.45) cm and in LUL group was 1.97±0.42 (1.20-2.60) cm. The duration of the operations were 94.13 ± 17.34 (75-140) minutes, and 121.43 ± 19.91 (90-167) minutes (P =0.001); and the average hospital stay days were 3.73 ± 1.20 (3-8) and 4.80 ± 1.71 (3-9) days (P = 0.017) in groups PCNUL and LUL, accordingly. The mean Hb decrease in PCNUL group was 1.16±0.35 mg/dL and in LUL group was 0.77±0.31 mg/dL (P = <0.001). No statistically significant differences in terms of fever and post operative prolonged urinary leakage were detected in both groups. Therefore the compared outcome is better in percutaneous nephroureterolithotomy group although stone clearance rate was same in percutaneous nephroureterolithotomy & laparoscopic ureterolithotromy patients. Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.25-30